FRACTURE EFFECTS ON SEISMIC ANISOTROPY FOR POROUS MEDIA DRIVEN BY ROCK PHYSICS - KOMARA (NIM: 22316010), EKI
Analysis of the effect of primary and secondary porosity from fractures is an important aspect for porous rock reservoirs such as tight sand and carbonate. The presence of fractures gives an anisotropy effect on seismic waves which depend on the azimuth and the incident angle. Seismic wave reflection response also variate depend on the primary porosity and the filling fluid. To determine the effect of primary porosity, fracture, and filling fluid on seismic reflection, rock physics modeling was carried out. There are two models commonly used to model media fractures, the penny shape model by Hudson (1980) and the linear slip model Schoenberg (1988). The Schoenberg model is more effective for rock physics modeling because can subtitute fluid directly on primary and secondary porosity and is not limited to small fracture densities. Rock physics modeling show that the primary porosity affects the anisotropy parameters because it increases the value of normal weakness parameter. By using the ratio between the normal and tangential weaknes parameters, the fracture filling fluid can be distinguished well on a small aspect ratio. Modeling reflection coefficients shows that the porosity decreases the amplitude response reflection coefficient and saturated rock brine gives the greatest amplitude response, while the smallest is saturated by gas.